KONSEP HUKUM PERDATA TERHADAP PERUSAHAAN YANG MEMBAYAR UPAH DI BAWAH STANDAR UPAH MINIMUM KOTA PALEMBANG MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Erniwati, Erniwati; Jhoni, Jhoni (Justici, 2024)
ABSTRACT Determination of the right to wages for workers or laborers in Law no. 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law is determined on the basis of units of output and units of time. Wages are important because wages are the main goal for workers/laborers in carrying out their work. Therefore, the government is also involved in dealing with wage problems. Workers/laborers will work well if they get good wages, therefore, in order for workers to be more productive, there needs to be good wages, so the role of law is very important, namely ensuring protection, especially in terms of providing wages for workers. The research in this paper is normative juridical research. Normative legal research or normative juridical research is library legal research carried out by examining library materials or secondary data. The results of this discussion both support and criticize the government's efforts to establish wage policies as an effort to realize the rights of workers/laborers to a decent living for humanity and is involved in ensuring the provision of legal sanctions for entrepreneurs who violate the laws and regulations in employment.